Efecto antioxidante in vitro de flavonoides totales del extracto fluído de hojas de sambucus peruviana H.B.K. (sauco) frente al 2,2-difenil-1-picrilhidrazil (DPPH) - Jiménez Garay, Jenny Marianella (2013)
In the present work investigaciónse prepared a fluid extract from the leaves of Sambucus peruviana HBK, which was performed phytochemical screening, testing for the presence of flavonoids. Likewise, purified and quantified the total flavonoids fluid extract obtained medianteel Kostennikova method described by Z. adapted by the Department of Pharmacognosy and pharmacobotany of the Faculty of Pharmacy and Biochemistry, UNT at 248 nm, being a percentage of 0.27% calculated as quercetin. Subsequently determined in vitro antioxidant capacity of total flavonoids obtained from the leaves of Sambucus peruviana HBK expressed as a percentage of radical scavenging by the method described by Brand-Williams, et; adapted by the Department of Pharmacognosy and pharmacobotany of the Faculty of Pharmacy and Biochemistry, UNT which served as the basis for the determination of IC 50 that had a value of 7.05 ug.